2006
DOI: 10.1128/cmr.00011-06
|View full text |Cite
|
Sign up to set email alerts
|

Coinfections Acquired from Ixodes Ticks

Abstract: SUMMARY The pathogens that cause Lyme disease (LD), human anaplasmosis, and babesiosis can coexist in Ixodes ticks and cause human coinfections. Although the risk of human coinfection differs by geographic location, the true prevalence of coinfecting pathogens among Ixodes ticks remains largely unknown for the majority of geographic locations. The prevalence of dually infected Ixodes ticks appears highest among ticks from regions of North America and Europe where LD is endemic, with reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
246
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(262 citation statements)
references
References 215 publications
(194 reference statements)
5
246
2
9
Order By: Relevance
“…Our result that high tick density areas had the highest overall prevalence of pathogens and the highest prevalence of coinfected ticks supports the fi nding of Hamer et al, who reported a signifi cant difference in the rates of pathogen carriage between recently invaded and I. scapularis-endemic areas (1). The rates of infection we found are similar to those found by Swanson et al from 5 other northeastern states (11). According to their metaanalysis, ≈40% (± 13%) of 2,109 adult and nymphal ticks were infected with B. burgdorferi, 21% (± 17%) with A. phagocytophilum, and 9% (± 8%) with either B. microti or B. divergens.…”
Section: Discussionsupporting
confidence: 89%
“…Our result that high tick density areas had the highest overall prevalence of pathogens and the highest prevalence of coinfected ticks supports the fi nding of Hamer et al, who reported a signifi cant difference in the rates of pathogen carriage between recently invaded and I. scapularis-endemic areas (1). The rates of infection we found are similar to those found by Swanson et al from 5 other northeastern states (11). According to their metaanalysis, ≈40% (± 13%) of 2,109 adult and nymphal ticks were infected with B. burgdorferi, 21% (± 17%) with A. phagocytophilum, and 9% (± 8%) with either B. microti or B. divergens.…”
Section: Discussionsupporting
confidence: 89%
“…was the only tick species identified on animals captured during this study, I. persculcatus ticks were present in these sampled areas suggesting that Borrelia spp. were also likely present in animal reservoirs captured [3]. The most common strains of Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the ecology of TBPs and their animal reservoirs is key to our understanding of disease epidemiology. While much is known about TBPs in developed settings [13], major gaps of knowledge remain regarding ticks and sylvatic transmission cycles in developing countries. This holds true in Mongolia, where a number of studies documenting tick diseases of clinical relevance have confirmed the presence of TBPs [412], but research regarding wild animal reservoirs has been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinfection with Babesia and Lyme disease is common. 1 Some suggest that ticks may host multiple infective agents and that this may increase the number of diseases a patient may present with after a tick bite. 2,3 This patient presented with symptoms and signs of 2 diseases.…”
Section: Discussionmentioning
confidence: 99%